Collision Tumour of the Ampulla of Vater: Carcinoid and Adenocarcinoma. Issue 4 (1997) - Williams, I. M.; Williams, N. W.; Stock, D.; Foster, M. E.
Abstract : Obstructive jaundice is most commonly due to luminal stones or lesions of the head of the pancreas and more rarely ampullary and primary common bile duct lesions. Obstruction due to lesions of the ampulla of Vater may be due to adenocarcinoma which has a significantly better long term prognosis than carcinomas located in the head of the pancreas. A case is presented where two tumours were identified at the ampulla of Vater of the resected specimen one an adenocarcinoma and the other a carcinoid tumour representing a collision tumour.